Association between energy intake and prognosis in Chronic Kidney Disease (CKD) stages 3–5: an ambispective cohort study - Di Yang; Huifen Chen; Yan Han; Yuhan Shen; Guixin Liang; Tao Zhou; Fang Tang; Lizhe Fu; Yifan Wu; Meizhu Ding (Renal Failure)
Background The association between dietary energy intake and disease outcomes in CKD 3–5 remains unclear. This study explored this relationship in Southern Chinese CKD 3–5 patients.Methods This retrospective cohort study included 234 CKD 3–5 patients from the Self-Management Program for Patients with Chronic Kidney Disease (SMP-CKD) database. The endpoint was a composite of sustained decline of at least 30% in estimated glomerular filtration rate (eGFR), the initiation of kidney replacement therapy, or all-cause mortality. The main variable was energy intake. Kaplan–Meier analysis, restricted cubic splines, and Cox regression models were performed to assess the association.Results 85 (36.3%) individuals reached the endpoint with a median follow-up of 33 months. The median age was 56.0 (46.3, 63.3) years, and 121 (51.7%) were male. The association between energy intake and the endpoint in CKD 3–5 patients showed a U-shaped relationship. We reclassified patients according to energy intake: Group 1 (<24.6 kcal/kg/d), Group 2 (24.6–29.5 kcal/kg/d), and Group 3 (>29.5 kcal/kg/d). Compared to Group 2, Group 3 (HR = 3.0; 95%CI, 1.118–7.993, p = 0.029) and Group 1 (HR = 2.5; 95%CI, 1.068–5.966, p = 0.035) had a higher risk of reaching the endpoint. Subgroup analysis showed no significant interaction except for age, with a consistent U-shaped relationship in those ≤ 60 years.Conclusion High and low energy intake are significantly associated with an increased risk of adverse outcomes in non-dialysis CKD 3–5 patients. An energy intake of 24.6–29.5 kcal/kg/day may be optimal to reduce the risk of poor health outcomes.